Counting Restricted Partitions of Integers Into Fractions: Symmetry and Modes of the Generating Function and a Connection to ω(t) - Hoelscher, Zachary; Palsson, Eyvindur (The PUMP Journal of Undergraduate Research, 2020)
Motivated by the study of integer partitions, we consider partitions of integers into fractions of a particular form, namely with constant denominators and distinct odd or even numerators. When numerators are odd, the numbers of partitions for integers smaller than the denominator form symmetric patterns. Such properties can be applied to a particular class of nonlinear Diophantine equations. Most importantly, we find that our restrictions enable an elementary proof of the unimodality of the nonzero terms of the generating function, which in general is quite hard. We also examine partitions with even numerators. We prove that there are 2ω(t) − 2 partitions of an integer t into fractions with the first x consecutive even integers for numerators and equal denominators of y, where 0 < y < x < t. We then use this to produce corollaries such as a series identity and an extension of the prime omega function to the complex plane.